96.7k views
4 votes
What is the answer for this question
3(a-7)=6a

2 Answers

2 votes
The answer to this is -7
User Racer
by
5.7k points
6 votes

Answer:a=-7

Explanation:The given equation is 3(a-7)=6a

Using distributive rule we have:

3a-21=6a

21 is subtracted to 3a .We always perform the opposite operation both sides.

Opposite of subtraction is addition

Adding 21 both sides

3a=6a+21

Subtracting 6a both sides:

3a-6a=21

-3a=21

Dividing both sides by -3 we have

a=-7.


User Paul Salber
by
5.8k points